Development of Water-Surface Robotic Vehicle to Assist Communication Between Remotely Operated Vehicle Underwater Robot and Control Station - Badrut Tamam; Ronny Mardiyanto (Department of Electrical Engineering ITS and FORTEI, 2017)
This paper developed a water-surface robotic vehicle that act as repeater station to assist the communication between ROV (Remotely Operated Vehicle) underwater robot and control station. The key issue here is how the robot can relay the data communication between the ROV and the control station. The communication between repeater Station and control station is based on wireless, whereas the communication between repeater Station and ROV is based on wire. Data that have transmit from control station is received by Repeater Station and continued to the ROV through wire. The Power needed is suplied by photovoltaic (PV) to the Repeater Station and the ROV. The position of Repeater Station is controlled, so the position of Repeater Station and ROV always in parallel. In practices, there are two way directly communication between control station with ROV, that are based on wireless and through wire. Nevertheless, wireless communication system never used to observed on the ocean or the deep waters because there is a high attenuation of a signal when cross the air-water boundary. Based on these problems, we make a Repeater Station that used a buoyant communication system models. Communication from control station to Repeater Station in the form of motion control and data. Whereas, communication from Repeater Station to ROV in the form of motion control, data, and power supply. Communication frequency is at 5,8 GHz for audio video and 433 MHz for motion control and telemetry. The connection wire between Repeater Station and ROV can go along and shorten with automatically roll as feature. Electricity from PV is strorage to a battery in the Repeater Station. Charging of the battery occur when battery power is not full and will cease if battery power is being full. Power of the battery must be full if want to operated the Repeater Station. The availability of the Repeater Station is expected to assist the communication between ROV underwater robot with control station, so ROV can be controlled remotely and can increase range of the reach.Keywords: Water-Surface Robotic Vehicle; Communication; Position Control; Repeater Station; Self Charging